ESG and Firm Value Linkage: A Case Study in the Automotive Industry - Ray, Samrat; Kumar, Dhirendra; Roy, Sumitra; Verma, Anil (Heca Sentra Analitika, 2024)
Environmental, social, and governance (ESG) performance and firm value are under scrutiny in this study, examining the impact of ESG factors on financial metrics. A survey was conducted, and the questionnaire was distributed to stakeholders within the automotive industry in India. Statistical analyses, including regression and correlation techniques, were employed to ascertain the connections between firm value and ESG performance. Strong correlations between ESG performance and financial indicators were observed. The findings underscore the significance of social responsibility practices in enhancing a company's trustworthiness, fostering trust among stakeholders, and maintaining long-term competitiveness. Furthermore, the study illustrates the integration of environmentally friendly business methods within the automotive industry. It emphasizes the importance of aligning ESG practices and social responsibility objectives with financial performance goals.